Regular Two-Dimensional Arrays of Surface-Mounted Molecular Switches: Switching Monitored by UV-vis and NMR Spectroscopy - Santos Hurtado, Carina; Bastien, Guillaume; Mašát, Milan; Štoček, Jakub Radek; Dračínský, Martin; Rončević, Igor; Císařová, Ivana; Rogers, Charles T; Kaleta, Jiří (Journal of the American Chemical Society, 2020)
Using solid-state 15N NMR spectroscopy, the cis/trans isomerization in a two-dimensional (2-D) array of surface-mounted azobenzene-based switches was detected for the first time. In order to achieve this, a new class of rod-shaped molecular switches, suitable for formation of 2-D regular arrays on large facets of tris(o-phenylenedioxy)cyclotriphosphazene (TPP) nanocrystals, was synthesized. A mechanochemical approach was used to prepare corresponding host-guest surface inclusions in a TPP matrix. Comparison of thermal steps in solution and supramolecular surface inclusions revealed that switching of individual molecules is not compromised by the close proximity of neighbors.